Development of an after-market universal fuel gauge for motorcycle - Maarof, M.I; Samoh, Ehsan; Girma, T. Chala; Rishan, Murali (IAEME Publication, 2018)
ASEAN countries have shown continuous increment in demand and usage of motorcycles. In addition as an alternative mode of transportation, motorcycle has become a cultural lifestyle and even status symbol for the citizens – especially for high-performance motorcycles. However, factory-installed fuel gauges are not available for most of these classes of motorcycles. They are only equipped with a warning light which triggers upon low fuel capacity. This study is aimed at designing and testing a universal after-market fuel gauge for motorcycles. The coupling of an ultrasonic sensor with an Arduino circuit board was utilized in developing the device. Both simulation and experimental assessments were carried out at flat and inclined surfaces to validate the accuracy of the device. It was observed that percentage errors between the experimental and simulation results were below 20%. The newly designed device with an accuracy of more than 80% would provide reasonable fuel measurement accuracy at low cost with user-friendly interface. Conclusively, the developed innovation is capable in providing a better motorcycling experience with respect to fuel measurement method and display